Nanomechanical, Structural and Antioxidant Characterization of Nixtamalized Popcorn Pericarp - Liliana Edith Rojas-Candelas; Mayra Díaz-Ramírez; Adolfo Armando Rayas-Amor; Rosy Gabriela Cruz-Monterrosa; Juan Vicente Méndez-Méndez; Adriana Villanueva-Carvajal; Alejandro de Jesús Cortés-Sánchez (Applied Sciences, 2022)
Expanded popcorn grain is widely consumed as a healthy snack all around the world; however, the study of the behavior of its components by processes such as nixtamalization is scarce. Therefore, the aim of this work was to characterize the nanomechanical, structural, and antioxidant properties of nixtamalized popcorn grain pericarp. FT-IR results showed that the secondary structure of proteins of the nixtamalized pericarp was α-helix with 42.10%, the turn was 21.5% and 36.33% β-sheet, and proteins of the pericarp did not present the random coil structure. Pericarp showed antioxidant activity, as their values were 550.1 ± 2.9 and 44.2 ± 1.6 (TE)/mL for ABTS and DPPH, respectively; total phenols content was 0.21 ± 0.008 (TE)/mL; reducing power values were around 29 to 31%; hydroxyl radical scavenging ranged from 36 to 55% and iron chelation around 115 to 140% compared to the standard acids. Thickness values of the nixtamalized pericarp by SEM image analysis were 0.15 ± 0.1 mm near the pedicel inferior tip, 0.07 ± 0.01 mm at middle, and 0.03 ± 0.02 mm at upper of the grain. Young’s modulus value was 261.72 ± 23.58 MPa with a Gaussian function fitting at the distribution of all values. This research provides novel and valuable information for understanding the nanomechanical and protein arrangement, as well as and the antioxidant activity of nixtamalized popcorn grain pericarp in order to promote other processes and uses for this kind of pericarp maize.